Hubungan Kekuatan Otot Lengan, Vo2 Max dan Persepsi Kinestetik Terhadap Akurasi Tembakan Jarak 50 Meter - Baskoro, Danar Arga (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to determine the relationship between the strength of the armmuscles against the accuracy of the shot, VO2 Max to the accuracy of the shot, the perceptionof kinesthetic the shot accuracy, strength of arm muscles, VO2 Max and perception kinestheticthe shot accuracy of 50 meters in athletes PPLP archery Central Java 2016 . this researchuses descriptive method with a correlation study. The results of this research are: 1) the relationshipbetween the strength of the arm muscles against the accuracy of the shot a distanceof 50 meters to get a yield of 0.152> 0.05, 2) the relationship between VO2 Max the shotaccuracy of 50 meters to get a yield of 0.02 <0.05 , 3) the relationship between the kinestheticperception of the accuracy of the shot a distance of 50 meters to get a yield of 0.190> 0.05,4) the relationship between the strength of the arm muscles, VO2 Max, and kinesthetic persesithe shot accuracy of 50 meters to get a yield of 0.063> 0.05 , Conclusions from this research isno significant correlation between the strength of the arm muscles, VO2 Max, and kinestheticpersesi the shot accuracy of 50 meters.